An experimental investigation on fracture parameters of recycled aggregate concrete with optimized ball milling method - Dilbas, Hasan; Cakir, Ozgur; Yildirim, Hasan (ELSEVIER SCI LTD, 2020)
In this paper, Ball Milling Method (BMM) is employed on recycled aggregate (RA) with an optimization process which is conducted to enhance RA efficiently eliminating attached old mortar (AOM) content in RA. Various combinations of drum rotation (R) (100-200-300-400-500) and the steel balls (S) (0-2-5-7-10-12) applied to the recycled aggregate during the BMM process and treated recycled aggregates (RAi) are obtained. The mechanical properties (compressive, splitting tensile and flexural strength values and elasticity modulus) and the non-linear fracture parameters (effective crack length, crack mouth opening displacement, crack tip opening displacement, initial cracking toughness, unstable fracture toughness and fracture energy) of concretes including untreated and treated recycled aggregate (RAi) are determined. The test results proved that the water absorption values of recycled aggregates in the size of 4-11.2 mm and 11.2-22.4 mm reduced from 8.80% to 1.40% and 8.95% to 0.84%, respectively, after treatment process. It is also found that the compressive strength of concretes are marginally affected with the use of treated recycled aggregate (RAi) up to 60% which is twofold of the optimum recycled aggregate proportion given in the literature. Moreover, 60% RAi content in concrete can be recommended in terms of fracture characteristics (a(c), CMODc, CTODc, K-ic(ini), K-ic(un) and G(F)). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Ball milling method; Optimization; Treated recycled aggregate; Mechanical properties; Fracture parameters; QUASI-BRITTLE FRACTURE; DOUBLE-K CRITERION; CRACK-PROPAGATION; SILICA FUME; BEHAVIOR; COARSE; QUALITY; RUBBER; Construction & Building Technology; Engineering; Materials Science